2015
DOI: 10.1063/1.4930865
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic point-of-care blood panel based on a novel technique: Reversible electroosmotic flow

Abstract: A wide range of diseases and conditions are monitored or diagnosed from blood plasma, but the ability to analyze a whole blood sample with the requirements for a point-of-care device, such as robustness, user-friendliness, and simple handling, remains unmet. Microfluidics technology offers the possibility not only to work fresh thumb-pricked whole blood but also to maximize the amount of the obtained plasma from the initial sample and therefore the possibility to implement multiple tests in a single cartridge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In addition, Mohammadi et al. reported interesting studies on DC electrokinetics‐based blood plasma separation in straight microchannels with varying cross sections.…”
Section: Straight Microchannels With Varying Cross Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Mohammadi et al. reported interesting studies on DC electrokinetics‐based blood plasma separation in straight microchannels with varying cross sections.…”
Section: Straight Microchannels With Varying Cross Sectionsmentioning
confidence: 99%
“…11E) [167] and blood cells from biomarkers [168] as well as nano to submicron particles [169], and so on. In addition, Mohammadi et al [170,171] reported interesting studies on DC electrokinetics-based blood plasma separation in straight microchannels with varying cross sections.…”
Section: Insulating Hurdles Patterned On the Sidewalls Of Microchannelsmentioning
confidence: 99%
“…Techniques using CTCs’ affinity, biophysical properties, microarray traps, and direct imaging have been developed and compiled extensively to separate, quantify and study CTCs (Ferreira, Ramani, & Jeffrey, ; Green et al, ; Hyun, Kim, Gwak, & Jung, ; Qian, Zhang, & Chen, ). Several types of CTC filters have been developed including those which utilize the principle of capturing based on antibody affinity for the EpCAM on the CTC surface (Cen, Ni, Yang, Graham, & Li, ), dielectric property of cancerous cells (Mohammadi, Madadi, Casals‐Terré, & Sellarès, ; Mohammadi, Zare, Madadi, Sellarès, & Casals‐Terré, ; Safavieh et al, ), separation based on the size difference between CTC and blood cells (Zheng et al, ), indirect isolation of CTC by separating non‐CTC cells (Madadi, Casals‐Terré, & Mohammadi, ; Mohammadi, Madadi, & Casals‐Terré, ; Ozkumur et al, ), and magnetic beads‐based capturing of cancer cells (Issadore et al, ). Yet, only a handful of these have reached the commercialization stage (Andree, van Dalum, & Terstappen, ; Cen et al, ; Gabriel, Calleja, Chalopin, Ory, & Heymann, ; L. Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, blood plasma has been extracted from diluted blood in a cross flow filter based device employing an active reversible electro-osmotic flow based unblocking technique. 22 This technique enables active pulsatile unblocking of the filter entrance and significantly improves efficiency of the cross flow filter.…”
Section: Introductionmentioning
confidence: 99%